Bottom-up proteomics analysis of the secretome of murine islets of Langerhans in elevated glucose levels. Issue 2 (14th December 2016) - Schmudlach, Andrew; Felton, Jeremy; Kennedy, Robert T.; Dovichi, Norman J.
Abstract : Glucotoxicity is a causative agent of type-2 diabetes, where high glucose levels damage the islets of Langerhans resulting in oxidative damage and endoplasmic reticulum stress. Abstract : Glucotoxicity is a causative agent of type-2 diabetes, where high glucose levels damage the islets of Langerhans resulting in oxidative damage and endoplasmic reticulum stress. We evaluated the secretomes of healthy CD-1 murine islets. Three experimental conditions were investigated in biological triplicate: a control incubated with 11 mM glucose, 1-day incubation with 25 mM glucose, and 2-day incubation with 25 mM glucose. An SDS-based, filter-aided sample preparation protocol was used to prepare secretomes for analysis. A total of 428 protein groups were identified across the nine samples. Each condition generated between 328–349 protein IDs and intracondition protein overlap was between 66–90% for the biological triplicates. 232 protein groups were identified in all three conditions with 184 quantified at least once in each condition. Significant expression changes were observed for proteins associated with the unfolded protein response, such as proteases, chaperones, and elongation factors, as well as proteins associated with peptide hormone processing and small molecule metabolism.